IMPLEMENTASI K13 PADA BIDANG STUDI IPS KELAS VIII di MTs FATHUL ANWAR DESA SUKA MAJU KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Ida Nurjannah; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Curiculum is a set of plan to setting about contents and ingredients of lesson and method to use as guidelines implementation study activity. At education Curiculum be a main point in support a success national education. In this matter, writer, lift a theme abot implementation k13 at Fathul Anwar Islamic junior high school at Suka Maju’ Village Tambusai subdictrict Rokan Hulu district. The purpose of this research is 1) To know about plan of implementation Social science at MTs Fathul Anwar 2) To know about process of study activity Social science at MTs Fathul Anwar 3) To know about evaluation of result lesson Social science at MTs Fathul Anwar 4) To know about problem that fait accompli of Social science’s teachers in face with K13. This research is use descriptive kualitative Method Kuantitative Method, Technic to collect the data that use observation technic, interview technic and documentation. The result of this research can be concluded that : The first, The plan of implementation at MTs Fathul Anwar that implementation has good and if take a percent hase stay at 92%. That stay at very good category. Process implementation of study activity social science also has get good predicate and if take a percent hase stay at 57%. That stay at good category. Evaluation of lesson Social at MTs Fathul Anwar that implementation also has get good predicate and if take a percent has stay at 55%. That stay at good category. The problem that fait accompli is lesson amenities and electricity.Key Words: Implementation, Curiculum 2013